Glued Nature: Sticker Albums with Animal and Plant Themes in Southeast Europe from an Ecohumanities Perspective - Đurđević, Goran (Poznańskie Studia Slawistyczne, 2022)
Collecting sticker albums is part of growing up, learning, and having fun formany children in Southeast Europe from the mid-1950, when the first picture albums appeared, until today. Among the most famous examples are sticker albums with plant and animal themes analyzed from ecohumanities perspectives, i.e., the permeation of Nature and Culture. While most authors start from the content ( textual and visual analysis ), the author of this paper takes a completely different perspective. After the analysis, four major periods are visible ( the early 1970s, second half of the 1980s, second half of the 1990s and early 2000s and the period from 2013 to 2018 ) in which the increase in the number and quality of the mentioned albums correlates with a greater presence of green policies and politics.